Comparison of secure messaging application (WhatsApp) and standard telephone usage for consultations on Length of Stay in the ED - Gulacti, Umut; Lok, Ugur (Applied Clinical Informatics, 2017)
Objective: Consultation, the process of an Emergency Physician seeking an opinion from other specialties, occurs frequently in the Emergency Department (ED). The aim of this study was to determine the effect of secure messaging application (WhatsApp) usage for medical consultations on Emergency Department Length of Stay (ED LOS) and consult time. Methods: We conducted a prospective, randomized controlled trial in the ED using allocation concealment over three months. Consultations requested in the ED were allocated into two groups: consultations requested via the secure messaging application and consultations requested by telephone as verbal. Results: A total of 439 consultations requested in the ED were assessed for eligibility and 345 were included in the final analysis: 173 consultations were conducted using secure messaging application and 172 consultations were conducted using standard telephone communications. The median ED LOS was 240 minutes (IQR:230-270, 95% CI:240 to 255.2) for patients in the secure messaging application group and 277 minutes (IQR:270-287.8, 95% CI:277 to 279) for patients in the telephone group. The median total ED LOS was significantly lower among consults conducted using Secure messaging application relative to consults conducted by telephone (median dif: -30, 95%CI:–37to-25, p<0.0001). The median consult time was 158 minutes (IQR:133 to 177.25, 95% CI:150 to 169) for patients in the Secure messaging application group and 170 minutes (IQR:165 to 188.5, 95% CI:170-171) for patients in the Telephone group (median dif: –12, 95%CI:-19 to-7,p<0.0001). Consultations completed without ED arrival was 61.8% in the secure messaging group and 33.1% in the Telephone group (dif: 28.7, 95% CI:48.3 to 66, p<0.001). Conclusions: Use of secure messaging application for consultations in the ED reduces the total ED LOS and consultation time. Consultation with secure messaging application eliminated more than half of in-person ED consultation visits.Gulacti U, Lok U. Comparison of secure messaging application (WhatsApp) and standard telephone usage for consultations on Length of Stay in the ED. Appl Clin Inform 2017; 8: 742–753 https://doi.org/10.4338/ACI-2017-04-RA-0064
Keywords: Consultation; WhatsApp; secure messaging application; length of stay; overcrowding; emergency department